EFFECTIVENESS OF THE JUMPA ARTIS PROGRAM IN IMPROVING PUBLIC SERVICE DELIVERY IN SEDATI DISTRICT, SIDOARJO REGENCY - Rachmad Dwi Prasetyo; Vidya Imanuari Pertiwi (SOSIOEDUKASI, 2025)
This study aims to analyze the effectiveness of the Jumpa Artis Program (Free Ball Pickup Service) in improving public service quality in Sedati District, Sidoarjo Regency. This program is an innovation in population administration services that provides direct services to villages to facilitate public access to documents such as e-KTP, Child Identity Cards, and Job Seeker Cards. The research uses a qualitative approach with a case study method, referring to Sutrisno's effectiveness theory which includes five indicators: program understanding, targeting accuracy, time accuracy, goal achievement, and real change. Data were collected through in-depth interviews with eight informants from district officials, Civil Registry Office, and community service recipients, as well as observations and documentation. The results show that this program is quite effective in increasing accessibility to population administration services, as evidenced by the increase in the number of service recipients from 100 people in 2021 to 160 people in 2024 with a satisfaction rate of 90 percent. The program successfully reached communities with limited access to district offices, reducing costs and time for document processing. However, there are still obstacles in implementation timeliness, inter-agency coordination, limited human resources and infrastructure, and suboptimal population data updates. This study recommends increasing HR capacity, adding infrastructure, developing digital information systems, and strengthening cross-sectoral coordination to improve program effectiveness sustainably.